2015
DOI: 10.1002/pssc.201400100
|View full text |Cite
|
Sign up to set email alerts
|

In situ UHVEM irradiation study of intrinsic point defect behavior in Si nanowire structures

Abstract: Si nanowire‐based Tunnel‐Field Effect Transistor (TFET) characteristics are intensively studied as function of nanowire diameter and doping. A significant reduction of B diffusion with decreasing nanowire diameter is e.g. observed and attributed to reduced transient enhanced diffusion close to the nanowire surface caused by the recombination and out‐diffusion of excess self‐interstitials. In an Ultra High Voltage Electron Microscope (UHVEM), the formation of self‐interstitial clusters can be studied in situ wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Irradiations are performed on FIB prepared cross-section samples between room temperature and 375 • C, using a 2 MeV electron beam. Some first results on the same structures were published elsewhere [16,17].…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Irradiations are performed on FIB prepared cross-section samples between room temperature and 375 • C, using a 2 MeV electron beam. Some first results on the same structures were published elsewhere [16,17].…”
Section: Introductionmentioning
confidence: 66%
“…3. More experimental results on the nanowires of the present study can be found in references [16] and [17].…”
Section: Samples For In Situmentioning
confidence: 95%
See 2 more Smart Citations
“…A first set of about 150 nm thick cross-section specimens for in situ irradiation was prepared by focused ion beam (FIB) both in the [110] and [100] orientations taking care that most of the nanowires were embedded into the sample thickness. Results on these samples have been published elsewhere [18][19][20].…”
Section: Sample Preparationmentioning
confidence: 99%